2013
DOI: 10.1021/nn405045x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Permeability and Mechanical Properties of DNA Origami Nanoplates on Solid-State Nanopores

Abstract: While DNA origami is a popular and versatile platform, its structural properties are still poorly understood. In this study we use solid-state nanopores to investigate the ionic permeability and mechanical properties of DNA origami nanoplates. DNA origami nanoplates of various designs are docked onto solid-state nanopores where we subsequently measure their ionic conductance. The ionic permeability is found to be high for all origami nanoplates. We observe the conductance of docked nanoplates, relative to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 32 publications
4
91
0
Order By: Relevance
“…Such protein-graphene hybrids or DNA origami-graphene structures [122][123][124] could provide means to control the motion of DNA molecules. Yet another alternative is to use plasmonics to control a DNA molecule in a nanopore [125,126].…”
Section: Discussionmentioning
confidence: 99%
“…Such protein-graphene hybrids or DNA origami-graphene structures [122][123][124] could provide means to control the motion of DNA molecules. Yet another alternative is to use plasmonics to control a DNA molecule in a nanopore [125,126].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by the Keyser [75] and Dekker [76] groups shows interesting voltage-dependent conductivity changes in nanopores modified by DNA-origamis (a DNA-origami is a nanostructure created by directed folding of DNA). For example, DNA-origami caps bearing a central aperture and dangling tails were trapped at the entrance of a glass nanopore under a positive applied potential bias.…”
Section: Figurementioning
confidence: 99%
“…The exact positioning of DNA origamis further enables a nanoscale platform, e.g., for examining single--molecule level reactions [21] or translocations of molecules [19,20]. In addition, studying mechanical [22] and electrical [22,23] properties of single DNA origamis becomes possible when the structures are precisely integrated into the measurement setup.…”
Section: Introductionmentioning
confidence: 99%
“…We used two straight brick--like shapes stacked either in square--(SQL) [33] or honeycomb lattice (HCL) [3] of DNA helices, and two other structures having either a curved 'C'--shape or an angular 'L'--shape in honeycomb lattice (HCL). Previous work has revealed that 2D and 3D origamis can be substantially deformed under high electric fields [18,22]. For this reason, we examined the influence of the trapping force (electric field gradient) on the structural deformation of the origamis and tuned the trapping parameters accordingly.…”
Section: Introductionmentioning
confidence: 99%